1993
DOI: 10.2307/3431849
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Responses of the Skin to External Stimuli

Abstract: The skin, in particular the epidermis, offers unique opportunities to investigate the induction and control of cellular proliferation and tissue homeostasis both under in vivo and in vitro conditions. Moreover, it represents one of the most feasible model systems for experimental cancer research. As the primary border of the body, the skin has important protective and defensive functions. A general response to external injury consists of a thickening of the epithelial layer (epidermal hyperplasia) combined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…From these data, COX-2 induced prostaglandin E 2 has been postulated to play a role in the development of skin cancer (Buckman et al, 1998). Consistent with this hypothesis, suppression of tumor development with a selective COX-2 inhibitor has been observed in mouse models of skin tumorigenesis (Marks and Furstenburger, 1993;MullerDecker et al, 1998a,b). In contrast to the data obtained in mouse models of skin cancer (Marks and Furstenburger, 1993;Muller-Decker et al, 1998a,b), we demonstrated that keratinocyte proliferation and differentiation following mild epidermal injury by abrasion were unaffected by inhibition of COX-2 or both COX isoforms.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…From these data, COX-2 induced prostaglandin E 2 has been postulated to play a role in the development of skin cancer (Buckman et al, 1998). Consistent with this hypothesis, suppression of tumor development with a selective COX-2 inhibitor has been observed in mouse models of skin tumorigenesis (Marks and Furstenburger, 1993;MullerDecker et al, 1998a,b). In contrast to the data obtained in mouse models of skin cancer (Marks and Furstenburger, 1993;Muller-Decker et al, 1998a,b), we demonstrated that keratinocyte proliferation and differentiation following mild epidermal injury by abrasion were unaffected by inhibition of COX-2 or both COX isoforms.…”
Section: Discussionsupporting
confidence: 60%
“…Consistent with this hypothesis, suppression of tumor development with a selective COX-2 inhibitor has been observed in mouse models of skin tumorigenesis (Marks and Furstenburger, 1993;MullerDecker et al, 1998a,b). In contrast to the data obtained in mouse models of skin cancer (Marks and Furstenburger, 1993;Muller-Decker et al, 1998a,b), we demonstrated that keratinocyte proliferation and differentiation following mild epidermal injury by abrasion were unaffected by inhibition of COX-2 or both COX isoforms. Furthermore, the epidermis became hyperplastic and returned to a normal, quiescent state with a similar time course in all treatment groups.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…2A, Right). The presence of infiltrating cells following incision was greatest between 24 h and 3 d, with the cellular immune response largely resolved between 7 and 10 d. Wound closure was observed by 2-3 d, along with a characteristic thickening of the epidermis at the site of injury (22,23). Some immune cells were still present within the dermal and, to a lesser extent, hypodermal layers 10 d after injury (the endpoint for incisional wounds).…”
Section: Resultsmentioning
confidence: 82%
“…In experimental studies of skin carcinogenesis, stimulation of epidermal cell proliferation alone is not a reliable predictor of tumor promotion; hyperplastic transformation with keratinocyte activation and the release of growth factors are critical for tumor development (20). A stochastic-based mathematical model of skin tumor promotion predicts that initiated cells may not exhibit a growth advantage over normal cells (21).…”
Section: Cell Proliferation and Modeling Organ-specific Carcinogenesismentioning
confidence: 99%